Exogenous spermidine elevating cadmium tolerance in Salix matsudana involves cadmium detoxification and antioxidant defense. Issue 4 (21st March 2019) - Tang, Chunfang; Zhang, Riqing; Hu, Xinjiang; Song, Jinfeng; Li, Bing; Ou, Danling; Hu, Xi; Zhao, Yunlin
Abstract: In this study, exogenous spermidine role on Salix matsudana tolerance to cadmium was evaluated. Spermidine and cadmium presented antagonistic effects on the biomass, copper and zinc concentrations in S. matsudana . cadmium mainly distributed in the cell wall of subcellular fraction; 46.97%–60.43% of cadmium existed in a sodium chloride-extracted form. Cadmium contents in roots, leaves, and twigs ranged from 2002.67 to 3961.00, 111.59 to 229.72, and 102.56 to 221.27 mg/kg, respectively. Spermidine application elevated cadmium concentrations in the roots, cuttings, and cell wall and the ratio of deionized water-extracted cadmium, but decreased cadmium levels in the twigs and leaves and the fractions of cadmium extracted by ethanol and sodium chloride, respectively. Putrescine and malondialdehyde were important indicators of cadmium-induced oxidative damage. Exogenous spermidine alleviated the accumulation of superoxide anion, hydrogen peroxide, malondialdehyde via promoting the levels of spermidine, soluble protein, superoxide dismutase, reductive ascorbate, glutathione reductase, and glutathione peroxidase in S. matsudana leaves under the corresponding cadmium stress. The results indicated that S. matsudana was a candidate for cadmium rhizoremediation and extraction in leaves; the spermidine application enhanced the cadmium tolerance of S. matsudana through promoting cadmium accumulation in roots, cell wall, and less bioactive chemical forms and the antioxidative ability.